The Effect of Family Center Nursing Education on Stunting Prevention Behavior Among Pregnant Women: A Study in East Kebundadap Village, Saronggi, Sumenep - Zakiyah Yasin; Ahmad Nawawi; Abd Wahid (Knowledge Dynamics, 2025)
Background: Accelerating stunting prevention remains one of the government's current priority programs. Prolonged nutritional deficiency occurring from the time a child is in the womb through the early stages of life during the first 1,000 days after birth can result not only in failure of physical growth and development, but also in impaired brain development, particularly during the gestational period. Increasing participation in family empowerment through family-centered nursing can help prevent stunting. This study aimed to analyze the effect of family-centered nursing-based education on stunting prevention behaviors among pregnant women in East Kebundadap Village. Methods: This study employed a pre-experimental research design with a one-group pre-post test design. The population consisted of pregnant women in their first through third trimesters along with one family member each. A total of 34 participants were recruited using simple random sampling. Data analysis was performed using the paired sample t-test with a significance level of p-value (α < 0.05). Results: The findings revealed that prior to receiving family-centered nursing education, the majority of pregnant women demonstrated poor preventive behaviors, whereas following the intervention, nearly all participants exhibited good preventive behaviors. The analysis of behavioral outcomes before and after family-centered nursing-based education yielded a p-value of 0.000 (α < 0.05), indicating a statistically significant effect on the behaviors of pregnant women following the educational intervention. Conclusions: Behaviors during pregnancy are supported by maternal attitudes and knowledge regarding their own pregnancies. Family-centered nursing-based education effectively assists pregnant women and their family members in positively influencing maternal behavior during pregnancy as it relates to stunting prevention.